It's getting hot in here : the past, present, and future of climate change - Heos, Bridget (Houghton Mifflin Harcourt, 2015)
"This hard-hitting look at climate change tackles the past, present, and future of global warming, examining the effects it's having across the world, the politics behind denial, and the ways in which we can all work to lessen the harsh effects of our warming world. Perfect for young environmentalists looking to learn about the ways in which we can take action against global warming"--